Measurements and Calculations of parametrs of Zinc Oxide Plasma Produced by Laser induced Breakdown Spectroscopy - Hammoud, Fatima K.; Aadim, Kadhim A. (Iraqi Journal of Science, 2022)
In this work, the optical emission characteristics of the ZnO plasma were presented. The plasma parameters: electron temperature (Te), electron density( ne), plasma frequency (fp) and Debye length (λD) were  studied with  a spectrometer that collects the spectrum ZnO plasma in air produced by Nd:YAG laser,(λ=1064 nm) at ratio X=0.5 in the range of energy of (700-1000 mJ), duration (10 ns). The Boltzmann plot methodwas employed to calculate the electron temperature (Te), while the Stark broadening  was used to determine the electron density (ne), Debye duration (λD), and plasma frequency (fp).  Te, ne, and fp were found  to increase  with the increase of laser energy.In contrast, (λD) decreased with laser energy increase. The resulting electron temperature calculation value was (1.908-2.084) eV.